Contribuição ao estudo das relações dos conectores maiores de próteses parciais removíveis com tecidos gengivais - Bacigalupo, João Carlos Carvalho de [UNESP] (Universidade Estadual Paulista (Unesp), 1994)
The effect in the gingival tissue of four distinctive types of relationships between the major conector and the gingival margin was investigated in eight subjects in association with the experimental gingivitis model. The subjects wore appliances constructed in acrylic resin (retained by means of embrasure hooks) throughout the day an night, except during meals. After the appliances had been placed, the subjects were abstained from any oral hygiene for twenty-one days. Records of the Plaque Index, Gingival Index and probing deplh were taken at baseline and at each week. Data showed that there was a small increase in the Plaque Index and Gingival Index for the four areas and that the degree of inflammation of the covered areas was higher in the area without relief

O efeito no tecido gengival de quatro tipos distintos de relacionamentos entre o concetor maior e a margem gengival foi investigado em oito indivíduos em associação ao modelo de gengivite experimental. Os pacientes utilizaram um aparelho confeccionado em resina acrílica retido por fios de aço diuturnamente, exceto às refeições. Após a colocação do aparelho os pacientes foram privados de qualquer procedimento de higiene oral por 21 dias. Registros do índice de placa, índice gengival e profundidade de sondagem foram tomados ao início e a cada semana. Os dados demonstraram que houve pequeno aumento no índice de placa e índice gengival para as quatro áreas e que o grau de inflamação das áreas recobertas foi maior na área sem alívio
Keywords: Periodontia; Placa dentária; Prótese parcial removível; Gengivite; Dental plaque